2023
DOI: 10.1111/aas.14299
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in older patients admitted to an ICU for COVID‐19: A systematic review

Abstract: PurposeThe objective was to conduct a systematic review of mortality and factors independently associated with mortality of older patients admitted to an intensive care unit (ICU) for COVID‐19.Materials and MethodsData sources were MEDLINE, EMBASE, the Cochrane Library, and references of included studies. Two reviewers independently selected studies evaluating mortality of older patients (≥ 70 years) admitted to an ICU for COVID‐19. They extracted general characteristics, mortality rate, and factors independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Patients with frailty (CFS 4–9) had a higher risk of mortality (OR = 3.12) and were less likely to be admitted to the ICU (OR 0.28) The authors then recommend that the CFS should be included in international Covid-19 treatment guidelines [ 69 ]. Another systematic review found that frailty in the ICU, assessed by the CFS, was significantly associated with 1 month and 3 month mortality respectively in two studies [ 70 ].…”
Section: Frailty In Critically Ill Over 75 Year-oldsmentioning
confidence: 99%
“…Patients with frailty (CFS 4–9) had a higher risk of mortality (OR = 3.12) and were less likely to be admitted to the ICU (OR 0.28) The authors then recommend that the CFS should be included in international Covid-19 treatment guidelines [ 69 ]. Another systematic review found that frailty in the ICU, assessed by the CFS, was significantly associated with 1 month and 3 month mortality respectively in two studies [ 70 ].…”
Section: Frailty In Critically Ill Over 75 Year-oldsmentioning
confidence: 99%